Coronary-intercostal steal syndrome, a rare connection between the left circumflex coronary artery and intercostal arteries: A case report - Habib, Mohammed H; Alkhodari, Khaled H (Journal of Cardiology and Cardiovascular Medicine, 2020)
A 60-year-old female patient presented with typical anginal pain on exertion and relieved by rest for about one month. Percutaneous coronary angiography was done and showed an abnormal left circumflex coronary artery connecting to intercostal artery. Embolization of that abnormal connection was done successfully and the patient discharged from hospital after 24 hours. This case shows a new form of coronary steal syndrome. This cause could be missed if not put under the differential diagnosis of typical anginal pain with normal coronary arteries.